Blockchain applications on mobile device: decentralized social media application - Wong, Isaiah Hao Jie (Nanyang Technological University, 2023)
The Ethereum blockchain has garnered widespread adoption in the blockchain space. With its feature rich developer tool kits and a developer oriented community, the Ethereum blockchain is an ideal platform to develop decentralized applications (dApp). This project focuses on building a proof-of-concept (POC) mobile based social media dApp, targeted at Nanyang Technological University (NTU) members. The dApp – named NTU Social, aims to improve the social experience for members through the integration of the Ethereum blockchain, leveraging on its immutability, ownership, and network effects. The following report defines the concepts and features of NTU Social, and the infrastructure and frameworks utilized to engineer NTU Social. In addition, the project introduces a hybrid approach of developing the dApp that adopts a centralized server, which acts as a relayer to the dApp to interact with the blockchain.